Bank Capital Regulation in a Zero Interest Environment - Robin Döttling (ZBW – Leibniz Information Centre for Economics, 2019)
How do near-zero deposit rates affect (optimal) bank capital regulation and risk taking? I study these questions in a tractable, dynamic equilibrium model, in which forward-looking banks compete imperfectly for deposit funding, subject to a (zero) lower bound constraint on deposit rates (ZLB). At the ZLB, capital requirements become less effective in curbing excessive risk-taking incentives, as they disproportionately hurt franchise values. As a consequence, optimal dynamic capital requirements vary with the level of interest rates if the ZLB binds occasionally. Subsidizing bank funding costs at the ZLB dampens risk-taking, but may reduce overall welfare.
Keywords: G21; G28; E43; 330; Zero lower bound; Search for yield; Capital regulation; Bank competition; Franchise value